Investigating the diversity of extracellular vesicle microRNA in response to exercise-induced muscle micro-damage: comparison of targeted plasma microRNA to targeted and in-depth analysis of extracellular vesicle microRNA - Lovett, Jason Andrew Charles (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.